Hurst and priority adaptive RED combined with dynamic scheduling algorithm based on AOS - Yu-xia BIE; Cheng-sheng PAN; Hai-yan LIU; Yan-chun WANG (Tongxin xuebao)
In order to efficiently transmit different types of high-capacity and burst data,based on virtual channel multiplexing technology on advanced orbiting systems(AOS),a Hurst and priority adaptive random early detection(RED) combined with dynamic scheduling algorithm named HPRED-DS was proposed.In queue management state,the algorithm designed an adaptive two-level packet dropping strategy based on Hurst parameter and priority.In virtual channel scheduling state,a VIP,synchronous and asynchronous mixed virtual channels scheduling mode was designed.Meanwhile,the algorithm efficiently combined queue management and virtual channel scheduling.Experimental results show that on the basis of maintaining high treatment efficiency and throughput,the algorithm stabilizes queue length,reduces delay and delay jitter,can meet various services’transmitting requirement.